IMPLEMENTATION OF PEKANBARU CITY REGULATION NUMBER 12 OF 2008 CONCERNING SOCIAL ORDER (CASE: HANDLING PROSECUTION) - Niki Astina Putri; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to analyze the implementation of Pekanbaru City Regional Regulation No. 12 of 2008 concerning social order (case: prevention of prostitutes) and to analyze the factors that become obstacles in the implementation of Pekanbaru City Regional Regulation No. 12 of 2008 regarding social order (case: prevention of prostitution). prostitutes). This research is a study that uses a qualitative methodology. This research is descriptive in nature, describes the reality correctly regarding the implementation of Pekanbaru City Regulation Number 12 of 2008 concerning social order (case: prevention of prostitutes). Qualitative research aims to reveal certain social situations by describing the true reality. The results of this study are the implementation of Pekanbaru City Regulation Number 12 of 2008 concerning social order (case: prevention of prostitutes) consisting of: 1) communication, between related agencies, namely Satpol PP and Pekanbaru Social Service, 2) resources, which consist of resources. human resources, budget and infrastructure, 3) behavior, attitude of responsibility, commitment, discipline and obedience in the implementation of local regulations, 4) bureaucratic structure, which can be seen from SOPs and clear division of tasks and responsibilities. The factors that become obstacles in the implementation of Pekanbaru City Regulation Number 12 of 2008 concerning social order (case: prevention of prostitutes) in the form of lack of socialization to the community, less resources in terms of quantity and budget constraints. Keywords: Implementation, Regional Regulations, Social Order, Prostitutes.